Perception and Use of School Library in Sharjah (U.A.E.): A Critical Case Study of India International School (IIS) and Providence English Private School (PEPS) - Parveen, Noushia (Library Waves, 2016)
The present study explains the perception about library and actual use of library in two schools comparatively (India International School, Sharjah and Providence English Private School, Sharjah) in critical way. The author has visited both schools and observed that there was great difference between perception and use of the library in the both school. The author has pointed out few things which can be improved. Author further provides critical analysis and empirical and theoretical observations about school environment and services to students and staff.